Rocuronium-induced anaphylaxis: a case report - Takahashi, Kanako (JA Clin Rep, 2019)
BACKGROUND: Neuromuscular blocking agents are frequently a cause of anaphylaxis that occurs in the perioperative period, and a skin prick test is an examination for definite diagnosis. CASE PRESENTATION: We report our experience of a patient with rocuronium-induced anaphylaxis who was scheduled to undergo open-heart surgery. After induction of anesthesia, anaphylaxis was suspected because the patient’s blood pressure decreased, airway pressure increased, and skin flushing and edema were observed on her neck and arms. With rapid treatment, good progress was seen without complications. About 5 weeks later, skin prick tests were performed for rocuronium and vecuronium. She was positive for rocuronium and negative for vecuronium. Seven weeks after anaphylaxis, vecuronium was used for the surgery and she had no symptoms that indicated anaphylaxis. The operation was completed uneventfully. CONCLUSION: We experienced a case of anaphylaxis caused by rocuronium. After a definite diagnosis had been made by a skin prick test, safe anesthesia management was possible using vecuronium during the reoperation.